Butakov B.I., Artyukh V.A. Analytical determination of mode treatment at rolling rollers by device from stabilizing working effort rolling. - Бутаков, Б.И.; Артюх, В.А. (Problems of Tribology, 2014)
Research on the choice of optimum effort of rolling-off, is it set that value of middle pressure , for torovivid, barrel-type and cylindrical rollers, certain at the different middle corners of pressing φ, deviates from hardness on Meyer no more than on 7 %. Does it allow to accept at a calculation efforts of rolling toroobraznymi, by barrel-type and cylindrical rollers as a condition of similarity constancy of middle corner of pressing φ, and also the optimum corners of pressing are set for the clean and consolidating mode of rolling-off and optimum linear effort of rolling-off from the diameter of roller is experimentally certain which will provide the roughness of surface on the treated detail of Ra = 0,63 – 1,25 mkm.